ANALISIS PENERAPAN PENDEKATAN SCIENTIFIC DALAM PEMBELAJARAN AL-QURAN HADIST KELAS XI MADRASAH ALIYAH BAHRUL ULUM DESA AIR EMAS KECAMATAN SINGINGI KABUPATEN KUANTAN SINGINGI - Sri Susanti; Zulhaini Zulhaini; Helbi Akbar (Universitas Islam Kuantan Singingi, 2020)
This study aims to conduct a study of the application of a scientific approach carried out by Quranic Hadith educators of class XI Madrasah Aliyah Bahrul Golden Water Village, Singingi sub-district, Kuantan district Singingi. This research uses a qualitative methodology, while the data collection was carried out at Madrasah Aliyah. Data collection techniques used interviews, observations, and documentation that are focused on the Quranic Hadith educators. Data validation is done by triangulation techniques. Data analysis techniques using descriptive analysis techniques include data collection, data reduction, presenting data, and making conclusions.The results of the study above state that the application of the scientific approach in learning the of Quranic Hadith educators of class XI Madrasah Aliyah Bahrul Golden Water Village, Singingi sub-district, Kuantan district Singingi. Overall has been running but not as complete as planning learning in the form of a learning plan (RPP) before learning. The lesson plans made in the implementation of learning activities are educators who have carried out preliminary activities, core activities, and closing activities. But educators have not fully carried out core activities, educators only apply 4 M out of 5 M is observing, questioning, reasoning, and communicating.